Comparison of European, African, Asian, and Other/Mixed Race American Children for the Association Between Household Income and Perceived Discrimination. - Assari, Shervin; Ayoubian, Ali; Caldwell, Cleopatra H. (International Journal of Travel Medicine & Global Health)
Introduction: Perceived discrimination is one of the reasons behind ethnic health disparities. However, less is known about racial and ethnic groups differ in social determinants of discrimination. This study aimed to compare the association between household income and perceived discrimination among American children of different racial groups. Methods: The Adolescent Brain Cognitive Development (ABCD) study, a national longitudinal study, followed 4383 children 9-10 years old who were either European American, African American, Asian American, or mixed/other race for one year. We compared racial groups for the association between baseline household income and perceived discrimination at the end of one year follow up. We used ANOVA and linear regression for data analysis. The outcome was perceived discrimination. The predictor was household income. Covariates were age, gender, and parental marital status. The moderator was race. Results: In the total sample, high household income was associated with less perceived discrimination. There was an interaction between race and household income, suggesting a difference in the association between household income and perceived discrimination between African American and European American children. The inverse association between household income and perceived discrimination was weaker for African American than European American children. Conclusion: High-income African American children are not well protected against perceived discrimination. High exposure to perceived discrimination may explain the worse expected health and development of middle-class African American children. As discrimination is a major social determinant of health, the results have considerable implications for public health policy.